Letter from Carl D. Duncan to Patricia Whiting, December 7, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Carl D. Duncan explains to Patricia Whiting why he admires her so greatly.